Vibrio Type Iii Secretion System 2 Is Not Restricted to the Vibrionaceae and Encodes Differentially Distributed Repertoires of Effector Proteins - Bravo-Zuniga, V (Microbiology Society, 2023)
Vibrio parahaemolyticus is the leading cause of seafood-borne gastroenteritis worldwide. A distinctive feature of the O3:K6 pandemic clone, and its derivatives, is the presence of a second, phylogenetically distinct, type III secretion system (T3SS2) encoded within the genomic island VPaI-7. The T3SS2 allows the delivery of effector proteins directly into the cytosol of infected eukaryotic cells to subvert key host-cell processes, critical for V. parahaemolyticus to colonize and cause disease. Furthermore, the T3SS2 also increases the environmental fitness of V. parahaemolyticus in its interaction with bacterivorous protists; hence, it has been proposed that it contributed to the global oceanic spread of the pandemic clone. Several reports have identified T3SS2-related genes in Vibrio and non-Vibrio species, suggesting that the T3SS2 gene cluster is not restricted to the Vibrion-aceae and can mobilize through horizontal gene transfer events. In this work, we performed a large-scale genomic analysis to determine the phylogenetic distribution of the T3SS2 gene cluster and its repertoire of effector proteins. We identified putative T3SS2 gene clusters in 1130 bacterial genomes from 8 bacterial genera, 5 bacterial families and 47 bacterial species. A hierarchical clustering analysis allowed us to define six T3SS2 subgroups (I–VI) with different repertoires of effector proteins, redefining the concepts of T3SS2 core and accessory effector proteins. Finally, we identified a subset of the T3SS2 gene clusters (subgroup VI) that lacks most T3SS2 effector proteins described to date and provided a list of 10 novel effector candidates for this subgroup through bioinformatic analysis. Collectively, our findings indicate that the T3SS2 extends beyond the family Vibrionaceae and suggest that different effector protein repertories could have a differential impact on the pathogenic potential and environmental fitness of each bacterium that has acquired the Vibrio T3SS2 gene cluster. © 2023 The Authors.